Development of Four-Tier Diagnostic Instruments to Identify Students’ Understanding of Electrolyte and Non-Electrolyte Solutions - Septiana Ayuningrum Nofinadya; Rima Nuraini; Isnanik Juni Fitriyah (STEM Education International, 2025)
This paper outlines the level of validity and reliability of a four-tier diagnostic instrument to identify the level of understanding of students on electrolyte and non-electrolyte solutions. The instrument development follows the stages proposed by Habiddin & Page (2019), namely mapping concepts, testing and interviewing, defining students' unscientific ideas, developing a four-tier prototype, validating the four-tier prototype, and refining the final four-tier instrument. The product eligibility percentage is 89.08%, which falls within the very feasible category.